Hubungan kurvilinear rujukan mulut dan persepsi kepuasan: kajian ke atas institusi bank di Malaysia - Ting, Ding Hooi (Universiti Utara Malaysia, 2003)
This paper is a study on the banking institution in Malaysia. The study is conducted due to recent developments on the satisfaction constructs where many researchers suggested that the satisfaction construct should be in a non-linear function and in a higher order (curvilinear) form as well as containing interaction effects. This means that the study on the satisfaction construct is a non linear function where bank ownership serves as the moderating variable. On top of this, the inclusion of bank ownership as the moderator has also shown that local bank ownership as the moderator has relationship between satisfaction and word of mouth referral. The Hierarchical Regression analysis has been utilized to test the moderating effect.This study has proven the existence of higher order form and also interaction effects.